Население Подонцовья эпохи Золотой Орды (по материалам могильников у села Маяки) - Ходжайов, Т.К.; Швецов, М.Л.; Ходжайова, Г.К.; Фризен, С.Ю. (Степи Европы в эпоху средневековья, 2012)
The authors have categorized archaeological and anthropological findings from burial grounds explored near Maiaki village (Tsarino hillfort) in the medium reaches of the Severskii Donets river. An analysis of the findings allows the authors to assert that the site was settled from the 7,h century to the 3rd quarter of the I4th century. The deceased were buried according to rites characteristic of different confessional population groups and anthropological types. Skulls from burials 8. 39 and 42 differ considerably from the other skulls found at the site; therefore, they could logically be classified in a separate cluster. In addition, complexes with these skulls display peculiar features of the funeral rite, thereby distinguishing it from all other burials of the site.